Year Round. Method of Speech Development and Correction - Pavlova, Y.B.; Khotyleva, T.Y. (Autizm i narušenie razvitiâ, 2018)
This methodological manual is created based on analysis of many years of experience of teachers working with children with developmental disorders. The manual is aimed at getting pre-school children or first graders with speech and communication difficulties leading to academic failure ready for school. Методическое пособие создано на основе анализа многолетнего опыта работы педагогов с детьми, имею-щими нарушения в развитии, и предназначено для подготовки к школе детей или для первоклассников, имеющих речевые проблемы и трудности в общении, что приводит к школьной неуспешности.